A comprehensive study of food waste management and processing in the Czech Republic: Potential health risks and consumer behavior - Vršanská, Martina; Veselá, Lucie; Baláková, Irena; Kovaříková, Ester; Jansová, Eva; Knoll, Aleš; Voběrková, Stanislava; Kubíčková, Lea; Vaverková, Magdalena Daria (The Science of the total environment, 2024)
Food waste is currently a widely discussed phenomenon with significant economic and social consequences. One third of the food produced in the world is wasted at various points along the food supply chain. This article presents a comprehensive study that examines consumer behavior in dealing with food waste and activities in the composting process that enable waste sanitation. The survey conducted as part of this study showed that consumers want to eliminate odors, are concerned about potential infections, and generally sort less food waste. This study suggested that the addition of appropriate additives could be a solution. The results indicated that additives could eliminate negative side effects such as unpleasant odors, the presence of insects and rodents, and act as a prevention of the occurrence of pathogenic organisms. Tea tree oil showed the best positive physical and chemical properties among the additives tested (CaCO3 and citric acid) with a significant effect on inhibiting the growth of bacterial strains such as Salmonella strains and had the strongest antibacterial effect, neutralized unpleasant odors, and stabilized the waste. The use of additives could be a future solution to meet consumer demands, improve the quality of food waste and advance the circular economy to improve the sustainability of agricultural systems.
Keywords: kompostování; Antibiotic sensitivity; chování spotřebitelů; Consumer Behavior; Microbiological analysis; Effects of various additives; Humans; Consumer willingness and challenges; nakládání s odpady; Food waste sorting; Czech Republic; Waste Management; Composting factors; Antibiotic resistance; lidé; Composting; Česká republika